Enhancing Mathematical Reasoning Skills Through Board Game Media and the Adaptive Problem-Based Learning Model - Kriswandani Kriswandani; Dani Kusuma (STAI Hubbulwathan Duri, 2025)
Mathematical reasoning is often underemphasized in basic education due to students’ difficulties in understanding mathematics. This study aims to develop and evaluate the effectiveness of board game media integrated with the Adaptive Problem-Based Learning (APBL) model in enhancing students’ mathematical reasoning skills. A mixed-methods approach was employed using a sequential exploratory design, beginning with qualitative research followed by a quantitative phase. The study was conducted at SD Kristen Satya Wacana (UKSW Laboratory) Salatiga. The developed board game, APBL model, and instructional materials underwent expert validation, yielding very high feasibility ratings of 84%, 95%, and 90%, respectively. The board game was then tested with 30 students, and data were collected through pretests, posttests, and practicality assessments. The implementation results showed a significant improvement in students' mathematical reasoning skills. The average pretest score of 62 increased to 84 in the posttest, reflecting a 35.48% achievement gain. Additionally, teacher and student responses in the practicality test yielded a 92% practicality score, categorized as very high. The findings indicate that integrating board game media with the APBL model effectively enhances mathematical reasoning. The model provides an engaging and structured learning experience that supports higher-order thinking skills while maintaining a practical and enjoyable classroom environment. The study concludes that board game media with the APBL model is highly effective and practical for improving mathematical reasoning. It is recommended for broader application across different education levels and learning contexts to enhance mathematics instruction.